Fixed right ventricular collapse: A loculated pericardial effusion due to metastatic pulmonary adenocarcinoma. (2023) - Smoot, Madeline; Reinoso, Jean Luis; Austin, Adam
Abstract: Pericardial effusions can occur as either circumferential or loculated when referencing their anatomic distribution in the pericardium. These effusions can result from multiple different etiologies, including malignancy, infection, trauma, connective tissue disease, acute pericarditis drug induced, or idiopathic. Loculated pericardial effusions can be difficult to manage. Even small loculated effusions can result in hemodynamic compromise. Oftentimes in the acute setting, point of care ultrasound can be used to evaluate pericardial effusions directly at the bedside. We present a case of a malignant loculated pericardial effusion and offer insight into management and clinical evaluation using point of care ultrasound.